Informational Efficiency and Information Subsets - LATHAM, MARK (Journal of Finance, 1986)
ABSTRACT This paper proposes a new definition of the Efficient Markets Hypothesis with respect to information, which is more formal and precise than those of Rubinstein [13] , Fama [4] , Jensen [6] , and Beaver [1] , and which fits well as a framework for interpreting the many tests of the Efficient Markets Hypothesis in the literature. Security markets are here considered “efficient with respect to information set ϕ ” if and only if revealing ϕ to all agents would change neither equilibrium prices nor portfolios. In addition to other desirable features, this definition has the “subset property”: efficiency with respect to ϕ implies efficiency with respect to any subset of ϕ .